ANALYSIS OF TEACHER READINESS IN IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT IN KINDERGARTEN DUREN SAWIT SUB-DISTRICT - Siti Rohmah; Siti Agustiani Rubiah; Sary Rina Naruvita; Noor Padilah; Rima Dewi Kartini; Titin Rahayu; Nita Priyanti; Chandra Apriyansyah (Universitas Panca Sakti Bekasi, 2023)
Curriculum changes are an absolute must to adjust to the times. The curriculum must continue to be developed and adapted according to the context and characteristics of students to build competencies that match what is needed in the present and the future. Teachers are one of the vanguard in realizing the implementation of curriculum changes in an institution because the key to successful learning in the classroom is influenced by teacher readiness in understanding and designing curriculum-guided learning. The purpose of this study is to describe the extent of teacher readiness in the implementation of the independent curriculum project to strengthen the profile of Pancasila students in TK Binaan 1 IGTKI, Duren Sawit District, East Jakarta, which began with workshops, coaching clinics, and mentoring by PAUD master students of Panca Sakti University Bekasi. The research method used is qualitative-descriptive. Based on the collection of analytical data, six indicators were proposed to determine the readiness of teachers for the implementation of the Pancasila student profile strengthening project. The six indicators are: Teacher understanding of the dimensions and elements of the Pancasila student profile; teacher readiness in designing concept maps; teacher readiness in making project modules; teacher readiness in preparing infrastructure; teacher readiness in designing and implementing project celebrations to strengthen the Pancasila student profile; and teacher readiness in designing and implementing assessments and reporting. The subjects of this study amounted to 32 people from 26 institutions. From the results of analysis through interviews, observations, and questionnaires, it can be stated that teacher readiness in the implementation of the independent curriculum averages 89.5% and that as much as 10.5% still needs to be improved. The implication of this research is that teachers are generally ready to implement the project of strengthening the profile of Pancasila students